2009
DOI: 10.1371/journal.ppat.1000678
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Yeast Cell Morphogenesis Is Regulated by a p21-Activated Kinase in the Human Pathogen Penicillium marneffei

Abstract: Pathogens have developed diverse strategies to infect their hosts and evade the host defense systems. Many pathogens reside within host phagocytic cells, thus evading much of the host immune system. For dimorphic fungal pathogens which grow in a multicellular hyphal form, a central attribute which facilitates growth inside host cells without rapid killing is the capacity to switch from the hyphal growth form to a unicellular yeast form. Blocking this transition abolishes or severely reduces pathogenicity. Host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…Recent studies have shown that pakA (Ste20p) plays a role during polarized conidial germination (discussed above), whereas pakB (Cla4p) is required for the signal to grow in the hyphal form at 25°C (6,32). Interestingly, deletion of pakB results in inappropriate yeast growth at 25°C, with colonies appearing yeastlike (compact and mucoid), with individual yeast cells evident (32).…”
Section: Fig 2 Life Cycle Of P Marneffei Shown Is a Representation mentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have shown that pakA (Ste20p) plays a role during polarized conidial germination (discussed above), whereas pakB (Cla4p) is required for the signal to grow in the hyphal form at 25°C (6,32). Interestingly, deletion of pakB results in inappropriate yeast growth at 25°C, with colonies appearing yeastlike (compact and mucoid), with individual yeast cells evident (32).…”
Section: Fig 2 Life Cycle Of P Marneffei Shown Is a Representation mentioning
confidence: 99%
“…Recent studies have shown that pakA (Ste20p) plays a role during polarized conidial germination (discussed above), whereas pakB (Cla4p) is required for the signal to grow in the hyphal form at 25°C (6,32). Interestingly, deletion of pakB results in inappropriate yeast growth at 25°C, with colonies appearing yeastlike (compact and mucoid), with individual yeast cells evident (32). While the ⌬pakB mutant shows decreased expression of hypha-specific genes and increased expression of yeast-specific genes at 25°C, deletion of brlA (primary regulator of asexual development) from the ⌬pakB mutant strain prevents the formation of yeast cells, suggesting that these cells arise inappropriately from the conidiation program (32).…”
Section: Fig 2 Life Cycle Of P Marneffei Shown Is a Representation mentioning
confidence: 99%
See 3 more Smart Citations